A Subchronic Toxicity Test of Dillenia ochreata Leaves Extract on Wistar rats: http://www.doi.org/10.26538/tjnpr/v7i11.32 - Muharni, Muharni; Choirunnisa, Nurnaili; Fitrya, Fitrya (Tropical Journal of Natural Product Research (TJNPR), 2023)
Dillenia ochreata were used traditionally to treat wounds and scabies. D. ochreata leaves have also been reported to have antibacterial, anti-inflammatory, and analgesic activities. This study aimed to determine the subchronic toxicity of an ethanol extract of D. ochreata leaves in Wistar rats. Tests were performed 28 days after administration of the extract. This study used 50 rats (25 males and 25 Females), each consisting of five groups: one control group (I) and four treatment groups (II-V) with doses of 100, 200, 400 and 800 mg/kg body weight (BW). Haematological parameters, biochemistry and histopathology of the liver, kidneys and heart were evaluated. The results showed that the treatment groups’ haematological levels and blood biochemical levels were still within normal, except for group V, which showed a significant difference (p <0.05) from the group I. The organ histopathology results in group V showed liver and kidney damage with fat degeneration and moderate necrosis in both male and female rats. Administration of the ethanol extract of D. ochreata leaves up to a dose of group IV showed no toxic symptoms, but toxic effects were shown at a dose of group V. The dose of 800 mg/kg BW (group V) of the ethanol extract of D. ochreata was found unsafe for use.